Rotordynamics analysis of solar hybrid microturbine for concentrated solar power - Maulana Arifin (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2020)
Microturbine based on a parabolic dish solar concentrator runs at high speed and has large amplitudes of subsynchronous turbo-shaft motion due to the direct normal irradiance (DNI) fluctuation in daily operation. A detailed rotordynamics model coupled to a full fluid film radial or journal bearing model needs to be addressed for increasing performance and to ensure safe operating conditions. The present paper delivers predictions of rotor tip displacement in the microturbine rotor assembly supported by a journal bearing under non-linear vibrations. The rotor assembly operates at 72 krpm on the design speed and delivers a 40 kW power output with the turbine inlet temperature is about 950 °C. The turbo-shaft oil temperature range is between 50 °C to 90 °C. The vibrations on the tip radial compressor and turbine were presented and evaluated in the commercial software GT-Suite environment. The microturbine rotors assembly model shows good results in predicting maximum tip displacement at the rotors with respect to the frequency and time domain.